2008
DOI: 10.1074/jbc.m805724200
|View full text |Cite
|
Sign up to set email alerts
|

Stress and IGF-I Differentially Control Cell Fate through Mammalian Target of Rapamycin (mTOR) and Retinoblastoma Protein (pRB)

Abstract: Significant discoveries have recently contributed to our knowledge of intracellular growth factor and nutrient signaling via mTOR (mammalian target of rapamycin). This signaling pathway is essential in cellular metabolism and cell survival by enhancing protein translation through phosphorylation of 4EBP-1 and p70S6K. Growth factors like insulin-like growth factor-I induce mTOR to prevent cell death during cellular stress. Agents targeting mTOR are of major interest as anticancer agents. We show here, using hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…These stresses are all independent of p38. In contrast, UV radiation, which activates stress pathways such as p38 and JNK through the induction of DNA damage, activates TORC1 in a number of cell types (7,48,75).…”
Section: Discussionmentioning
confidence: 99%
“…These stresses are all independent of p38. In contrast, UV radiation, which activates stress pathways such as p38 and JNK through the induction of DNA damage, activates TORC1 in a number of cell types (7,48,75).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, phosphatase activity has been shown to be required to cause apoptosis by UV stress or chemotherapeutic agents, such as etoposide and Ara-C. 13,16,21 In these studies, phosphatase inhibitors blocked both Rb dephosphorylation and apoptosis. Protein phosphatase 1 (PP1) is the primary phosphatase of Rb, responsible for the dephosphorylation of Rb at mitotic exit.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] In addition, UV stress and cdk inhibition that leads to apoptosis results in dephosphorylation of Rb. 17,18,21 Here, we show in MCF7 breast cancer cells and HCT116 colon cancer cells that various apoptotic stimuli cause dephosphorylation of Rb (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-proliferative activity of Rb is mediated via interaction with the E2F family of transcription factors which regulate both the G1 to S phase transition and stimulation of apoptosis (9,11). However, when proliferating cells are treated with apoptotic stimuli, Rb becomes dephosphorylated due to the activation of PP1 which can lead to cell cycle arrest and/or apoptosis (12)(13)(14). Activity of PP1 is controlled by association with regulatory subunits responsible for the substrate specificity, localization and activity of the PP1 catalytic subunit (15).…”
Section: Introductionmentioning
confidence: 99%